2021
DOI: 10.1039/d0tb02410d
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small gold nanoparticles self-assembled by gadolinium ions for enhanced photothermal/photodynamic liver cancer therapy

Abstract: Gold nanomaterials are widely used in biomedical research as drug delivery systems, imaging agents and therapeutic materials owing to their unique physicochemical properties and high biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In vivo treatment results fully prove that the nanoprobe has achieved satisfactory therapeutic effects after laser irradiation mediated photothermal/photodynamic combination treatment. The main organs of each treatment group did not show obvious pathological damage, proving that this nanoprobe has excellent in vivo biocompatibility [78].…”
Section: Applications In Cancer Treatmentmentioning
confidence: 83%
See 1 more Smart Citation
“…In vivo treatment results fully prove that the nanoprobe has achieved satisfactory therapeutic effects after laser irradiation mediated photothermal/photodynamic combination treatment. The main organs of each treatment group did not show obvious pathological damage, proving that this nanoprobe has excellent in vivo biocompatibility [78].…”
Section: Applications In Cancer Treatmentmentioning
confidence: 83%
“…The nanoparticles functioning as probes, T1 MRI, and in vivo fluorescence imaging modes showed excellent results. These nanoprobes can theoretically escape from the body due to their acid response degradation characteristics [78]. A study about gadolinium-conjugated gold nanoshells in multimodal diagnostic imaging showed their functionality as contrast agents in MRI, X-ray, and three optical imaging methods: OCT, RCM, and TPL.…”
Section: Gadolinium Nanoparticles In Therapymentioning
confidence: 99%
“…In vivo investigations showed that the nanomaterials attainted improved synergistic PDT-PTT therapies under laser treatments and effectively reduced tumor growth. From this study, it concludes that the gold nanostructure-based nanosystem has great efficiency against liver cancer with a dual imaging system [ 196 ]. Synergistic phototherapies have been shown to encourage therapeutic efficiency against various types of cancers.…”
Section: Synergetic Phototherapies Based On Gold Nanostructuresmentioning
confidence: 99%
“…Furthermore, spherical gold nanoparticles can also self-assemble into three-dimensional nanostructures for cancer treatment. In a recent study, You’s group reported nanoprobes formed by self-assembly of ultrasmall AuNPs for dual-mode real-time imaging-guided photothermal/photodynamic combined therapy for liver cancer [ 36 ]. The nanoprobes demonstrated excellent tumor-targeting capabilities in both T1 magnetic-resonance imaging and in vivo fluorescence imaging modes; meanwhile, the nanoprobes are able to dissociate and escape from the body to reduce aggregation in the body to minimize the possible toxicity [ 36 ].…”
Section: Gold Nanostructures For Cancer Treatmentmentioning
confidence: 99%